PENGARUH KECUKUPAN MODAL, PEMBIAYAAN, EFISIENSI BIAYA, RESIKO PEMBIAYAAN, DAN KUALITAS AKTIVA PRODUKTIF TERHADAP RETURN ON ASSETPADA BANK UMUM SYARI’AH PERIODE 2012-2016 - DwiPolahWicaksonowati, 13.05.52.0249; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2018)
This research was aimed and analyze at examining the influence of Capital Adequacy ratio, Financing to Deposit Ratio, Operating Expenses per Operating Income, Non Performing Financing, and Allowance for Earning Assets to profitability in Islamic Commercial Banks.  Research conducted a quantitave study with the entire population of Islamic Banks registered in Financial Fervices Autority (OJK) on 2012-2016, by  using  purposive  sampling  method. Types  of  data  used  are  secondary  data  obtained  from  published  financial statement  and  downloaded  through  the  official  website  of  Islamic Commercial Banks. The method of analysis used is Multiple Regression with a significance level of 5%. From the results of the analysis show that  Capital Adequacy Ratio , Operating Expenses per Operating Income, Allowance for Earning Assets has  significant influence to profitability, while Financing to Deposit Ratio,  and Non Performing Financing have not significant influence to profitability. Keyword : Capital Adequacy Ratio, Financing to Deposit Ratio, Operating Expenses per Operating Income, Non Performing Financing, Allowance for Earning Assets,   Return On Assets